Tunable high power fiber laser using an AWG as the tuning element - Latif, Amirah Abdul; Ahmad, Harith; Awang, Noor Azura; Zulkifli, Mohd Zamani; Pua, Chang Hong; Ghani, Zawajer A.; Harun, Sulaiman Wadi (IOP Publishing, 2011)
In this paper, a design of a High Power Tunable Fiber Laser (HP-TFL) in C-band region from 1536.7 to 1548.6 nm is set forth with Erbium Doped Fibers (EDFs) being used as a seeding signal and a booster amplifier. With a 1 × 16 channels Arrayed Waveguide Grating (AWG), this setup is capable of generating 16 different wavelengths with an average output power of 20.7 dBm.